Pass finals - Smith, Geoff; Carty, Elizabeth; Langmead, Louise (Edinburgh : Saunders Elsevier, 2013)
Pass Finals is a notes-style summary of the key facts to know for the diagnosis and management of important diseases. The book relates to Kumar & Clark's Clinical Medicine, and it's synoptic approach is intended to help time-poor students with revision for final exams in medicine. Information is presented as bullet point lists and short summaries. There are also practice self-assessment questions at the end of each chapter, with explanatory answers at the end of the book. Focuses on the most important medical specialities, including cardiology, neurology, GI, and rheumatology.
Register
Keywords: lekárstvo klinické; lekárstvo; učebnica